Community-Driven Identification and Adaptation of a Cancer Caregiving Intervention for LGBTQIA Populations - Kamen, Charles S.; Hastert, Theresa A.; Mulvaney, Megan; Hosea, Forrest; VanBergen, Alexandra M.; Fakih, Ali; Larkin, Knoll; Killingsworth, Evan; Thompson, Hayley S. (Frontiers in Oncology, 2022)
Background: Lesbian, gay, bisexual, transgender, and other LGBTQIA cancer patients experience significant disparities in cancer-related outcomes. Their relationships may not be acknowledged in care systems designed to serve primarily heterosexual and cisgender (H/C) patients, and resources for partners and caregivers of H/C patients may not address the needs of LGBTQIA caregivers. Tailored interventions are needed to address disparities in LGBTQIA patients and caregivers. Methods: To address this gap, researchers from Karmanos Cancer Institute in Detroit, MI and Wilmot Cancer Institute in Rochester, NY worked with a cancer action council (CAC) of LGBTQIA stakeholders with lived experience of cancer in a community-academic partnership. This group used the ADAPT-ITT model to guide their process of assessing needs in this community, identifying evidence-based interventions that could be adapted to meet those needs, and beginning the process of adapting an existing intervention to meet the needs of a new population. Results: In the Assessment phase of the model, CAC members shared their own experiences and concerns related to cancer and identified cancer caregiving as a priority area for intervention. In the Decision-Making phase of the model, researchers and CAC members performed a review of the literature on interventions that reported outcomes for cancer caregiver, identifying 13 promising interventions. Each of these interventions was evaluated over a series of meetings using a scoring rubric. Based on this rubric, the FOCUS intervention was established as an appropriate target for adaptation to the LGBTQIA population. In the first stage of the Adaptation phase, CAC members reacted to the intervention content and identified principal components for adaptation. Conclusion: While the FOCUS intervention adaptation is still in process, this manuscript can serve as a guide for others establishing community-academic partnerships to adapt interventions, as well as those developing interventions and resources for LGBTQIA persons coping with cancer.